The Influence of Work Environment, Work Motivation, and Collaborative Learning Practices on Teacher Performance in Public Junior High Schools in Berau Regency - Haeruddin, Haeruddin (Borneo Educational Journal (Borju), 2025)
Teacher performance refers to the ability of educators to effectively and efficiently fulfill their duties and responsibilities to achieve predetermined learning objectives. This study was conducted on 30 teachers from three public junior high schools in Tanjung Redeb District, Berau Regency at SMP Negeri 1, SMP Negeri 5, and SMP Negeri 6 to examine the influence of the work environment, work motivation, and collaborative learning practices on teacher performance in these schools. The findings revealed significant correlations between a conducive work environment (Mean = 104.30), strong teacher work motivation (Mean = 62.70), effective collaborative learning practices (Mean = 78.40), and teacher performance (Mean = 132.90). The purpose of this research was to identify factors influencing teacher effectiveness in public junior high schools in Berau Regency, where challenges related to teacher motivation are frequently encountered. Data collection was conducted using questionnaires validated through Product Moment and tested for reliability using Cronbach's Alpha (ranging from 0.586 to 0.955). A linearity test confirmed a significant relationship between the work environment and teacher performance (F = 16.931, p = 0.006). Based on data from the sampled teachers, overall teacher performance was rated high, with an average score of 132.90 well above the theoretical mean of 80 indicating a high level of effectiveness among the participants. Individual scores ranged from 82 to 159, with good teaching quality contributing to a positive learning environment and improved student outcomes in these schools. A supportive work environment emerged as a crucial factor in enhancing teacher performance. To sustain and further improve teacher effectiveness, schools should continue enhancing facilities, providing support to teachers, and fostering collaborative learning practices that benefit both educators and students alike